2014
DOI: 10.1155/2014/247693
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography in the Evaluation of the Primary Tumor in Patients with Cholangiocarcinoma: A Meta-Analysis

Abstract: Objective. To meta-analyze published data about the diagnostic accuracy of fluorine-18-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) or PET/computed tomography (PET/CT) for primary tumor evaluation in patients with cholangiocarcinoma (CCa). Methods. A comprehensive literature search of studies published through December 31, 2013, was performed. Pooled sensitivity and specificity were calculated on a per patient based analysis. Subgroup analyses considering the device used (PET versus PET/CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…However, one recent study showed PET/CT to be accurate in primary CCA evaluation, especially for intrahepatic compared with extrahepatic CCA,38 a finding that is similar to that of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…However, one recent study showed PET/CT to be accurate in primary CCA evaluation, especially for intrahepatic compared with extrahepatic CCA,38 a finding that is similar to that of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…5). 36 18 F-FDG-positron emission tomography (PET) with CT (PET/CT) has a sensitivity and specificity of up to 95% and 83% in the evaluation of the primary tumor, but it does not provide a significant advantage over CT or MRI 37. Also, positive FDG-uptake can be observed in other malignancies (i.e., lymphomas), inflammatory and infectious processes.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Regarding primary tumour detection in PET/CT, a meta-analysis of 1,232 patients in 23 studies provided high sensitivities of 95% and specificities of 83% for iCC [61], with a decrease to 84% and 76% in sensitivity and to 95% and 74% in specificity being found when evaluating pCC and eCC, respectively. This indicates a dependency of primary tumour evaluation on tumour localization.…”
Section: Positron Emission Tomography/ Computed Tomographymentioning
confidence: 99%